2020
DOI: 10.1210/clinem/dgaa214
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Radioiodine in Toxic Multinodular Goiter: Thyroid Volume, Function, and Autoimmunity

Abstract: Context Long-term studies evaluating the treatment of toxic multinodular goiter (TMNG) with fixed activities of radioiodine (RAI) are lacking. Objective The objective of this work is to describe the effects of 15 mCi on thyroid volume, function, and autoimmunity in the long term. Design and Setting A population-based, retrospective analysis with up to 12 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
5
3
0
1
Order By: Relevance
“…Other studies have also shown that the presence of antithyroid antibodies and unsuppressed TSH at the time of 131 I treatment increases the chance of progression to hypothyroidism. 7,10,20 In the present study, antithyroid antibodies were positive in only 9 of 96 patients (9.4%), but their presence did not influence the therapeutic response, as also described by Roque et al 18 In the group of responder patients who remained in euthyroidism up to 12 months after 131 I, a small portion had a recurrence of hyperthyroidism (6.1%), and 16% evolved with hypothyroidism, highlighting the importance of clinical and laboratory follow-up. Indeed, previous studies 7,16 showed that the late cumulative rate of hypothyroidism after a single 131 I dose increases progressively, reaching almost 50% (72/147 cases) after up to 20 years of follow-up.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Other studies have also shown that the presence of antithyroid antibodies and unsuppressed TSH at the time of 131 I treatment increases the chance of progression to hypothyroidism. 7,10,20 In the present study, antithyroid antibodies were positive in only 9 of 96 patients (9.4%), but their presence did not influence the therapeutic response, as also described by Roque et al 18 In the group of responder patients who remained in euthyroidism up to 12 months after 131 I, a small portion had a recurrence of hyperthyroidism (6.1%), and 16% evolved with hypothyroidism, highlighting the importance of clinical and laboratory follow-up. Indeed, previous studies 7,16 showed that the late cumulative rate of hypothyroidism after a single 131 I dose increases progressively, reaching almost 50% (72/147 cases) after up to 20 years of follow-up.…”
Section: Discussionsupporting
confidence: 83%
“…Regarding the change in thyroid volume after 131 I treatment, more than half showed a volume decrease greater than 40%, a result similar to that obtained in other studies. 2,18,21,22 It is noteworthy that 131 I treatment was well tolerated, with an adverse effect occurring around 2.4%, slightly higher than that described by other authors. 7 The major limitation of the present study is that it is retrospective.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…I gozzi molto grandi con associati sintomi compressivi o con noduli maligni sono indirizzati all'intervento chirurgico. Il trattamento radiometabolico con 131 I rappresenta, invece, un'opzione terapeutica molto valida in caso di adenomi tossici o di gozzi multinodulari tossici [19]. Lo iodio radioattivo si concentra, infatti, quasi esclusivamente nei noduli con autonomia funzionale, determinandone la distruzione con risoluzione dell'ipertiroidismo e notevole riduzione dimensionale.…”
Section: Trattamentounclassified